2018
DOI: 10.1007/s00404-018-4723-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral contraceptives and risk of hemorrhagic stroke: a meta-analysis of observational studies

Abstract: This meta-analysis of observational studies suggests that current use of OCs could contribute to a small increased risk of hemorrhagic stroke, and the increased risk is related to subarachnoid hemorrhage, but not intracerebral hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 36 publications
2
30
1
5
Order By: Relevance
“…Twenty three reviews reported overlapping associations. 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 Overlapping associations included: current use of combined oral contraceptives and risk of myocardial infarction, n=2 55 56 ; use of combined oral contraceptives and risk of ischaemic stroke, n=3 55 56 67 ; use of combined oral contraceptives and risk of haemorrhagic stroke, n=2 56 71 ; use of progesterone only pill and risk of stroke, n=2 72 73 ; use of combined oral contraceptives in migraine and risk of stroke, n=2 74 75 ; early menarche and mortality from cardiovascular disease, n=2 76 77 ; early menopause and risk of fatal cardiovascular disease, n=3 57 58 59 ; pre-eclampsia and risk of cardiovascular disease, n=2 60 61 ; gestational diabetes and risk of cardiovascular disease, n=3 62 63 69 ; preterm birth and risk of cardiovascular disease, n=3 60 64 65 ; and polycystic ovary syndrome and risk of cardiovascular disease, n=3. 66 68 70 Appendix 8 describes the general characteristics of the reviews with overlapping associations, including the decision to retain or exclude an association from the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty three reviews reported overlapping associations. 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 Overlapping associations included: current use of combined oral contraceptives and risk of myocardial infarction, n=2 55 56 ; use of combined oral contraceptives and risk of ischaemic stroke, n=3 55 56 67 ; use of combined oral contraceptives and risk of haemorrhagic stroke, n=2 56 71 ; use of progesterone only pill and risk of stroke, n=2 72 73 ; use of combined oral contraceptives in migraine and risk of stroke, n=2 74 75 ; early menarche and mortality from cardiovascular disease, n=2 76 77 ; early menopause and risk of fatal cardiovascular disease, n=3 57 58 59 ; pre-eclampsia and risk of cardiovascular disease, n=2 60 61 ; gestational diabetes and risk of cardiovascular disease, n=3 62 63 69 ; preterm birth and risk of cardiovascular disease, n=3 60 64 65 ; and polycystic ovary syndrome and risk of cardiovascular disease, n=3. 66 68 70 Appendix 8 describes the general characteristics of the reviews with overlapping associations, including the decision to retain or exclude an association from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Current use of any oral contraceptives (combined oral contraceptives and progesterone only pill), recurrent pre-eclampsia, and pre-eclampsia were associated with a twofold or more increased risk of stroke; maternal delivery of preterm infants, gestational diabetes, and current use of combined oral contraceptives were associated with a 1.5-1.9-fold increase in risk; and polycystic ovary syndrome was associated with a less than 1.5-fold increase in risk ( fig 6 ). 55 57 59 60 61 63 64 67 71 72 76 85 88 96 97 98 99 102 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that part of the study group were women using various forms of hormonal contraception (40.4%). The latest reports about mixing hormone-based contraceptives with nicotine confirm an increased risk of hemorrhagic stroke in women who smoke cigarettes and use oral contraceptives [21,22]. Another study investigating the attitudes of women using hormonal contraceptives towards quitting smoking has revealed that only 10% of them stopped smoking after starting to use hormone-based contraception, whereas the remaining 90%, by continuing to smoke, increased their risk of venous thromboembolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis indicated that the risk of first-ever ischemic stroke (IS) was increased significantly in females currently taking OCPs (11). Similarly, another meta-analysis study showed that current OCP use led to a small increase in hemorrhagic stroke (HS) incidence (12). Although Roach et al found that the OCP users were not at increased risk of IS, they stratified their meta-analysis according to estrogen dose and found that there was significant risk of stroke in women taking combined OCPs with estrogen doses more than 50 μg (13).…”
Section: Introductionmentioning
confidence: 99%